Clinical pathways on a mobile device. Issue 4 (12th November 2019) - Barrett, John; Turner, Barbara; Silva, Susan; Zychowicz, Michael
Abstract : Clinical pathways have been successfully implemented in the primary care setting in New Zealand, Australia and the UK. Despite wide adoption and decreased costs, these pathways have yet to translate evidence into clinical practice while also saving providers time—an important barrier for the translation of evidence at the point of care. The goal of this project was to determine if future development of a point-of-care mobile application should be undertaken with design principles using the theoretical framework of Hick's law. Three new-to-practice providers participated in three plan-do-study-act cycles using these pathways installed on mobile devices to determine if they were a feasible, efficient and useful method to implement evidence. The project was a success with all three participants wishing to continue using the pathways after project completion. Participants felt the digital clinical pathways were the next evolution of the popular UpToDate software platform and helped them apply the latest evidence better than other available tools. While these results are promising, there were also limitations. Participants felt the lack of chart integration coupled with time constraints made full integration challenging and suggested launching the platform using a variety of delivery systems. The project's findings suggest that future application development using the developed design principles would be worth further consideration. If this mobile application ultimately proved successful, the application framework could be implemented on a larger scale, thus improving patient outcomes and saving providers time.